Peningkatan Daya Saing Sdm Lokal Melalui Pendampingan Kompetensi Kerja Berbasis Kebutuhan Nyata Masyarakat - Taufik Hermansyah; Lati Sari Dewi; Siti Amirah Makarim (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This community service program aims to enhance the competitiveness of local human resources in Buanamekar Village, Ciamis Regency, through work competency assistance based on real community needs. The village faces challenges such as low digital literacy and limited access to formal certification, which hinder economic growth. The methods used include participatory situation analysis, competency-based training (CBT), and intensive mentoring. The results show a significant improvement in participants’ technical and soft skills, with an average post-test score increase of 45%. Furthermore, the program successfully established a local competency forum to ensure sustainability. This initiative proves that tailored competency assistance can effectively bridge the gap between local skills and market demands, thereby fostering sustainable rural development.